THE FUNCTIONAL STATE OF THE CARDIOVASCULAR SYSTEM OF ADOLESCENTS UNDER VARIOUS PHYSICAL ACTIVITIES (Web of Teachers: Inderscience Research, 2024)
A scientific study was conducted on students from grades 7 to 10, 3 boys and 3 girls were selected from each class, in which various indicators of the functional state of adolescents were measured. The total number of students who took part in the scientific experiment is 48 students.